Oncolytic vesicular stomatitis virus alone or in combination with JAK inhibitors is effective against ovarian cancer - Karen Geoffroy; Victor Mullins-Dansereau; Kim Leclerc-Desaulniers; Mélissa Viens; Marie-Claude Bourgeois-Daigneault (Molecular Therapy: Oncology, 2024)
Therapy-resistant ovarian cancers have a poor prognosis and novel effective treatment options are urgently needed. In this study, we evaluated the therapeutic efficacy of the oncolytic vesicular stomatitis virus (VSV) against a panel of patient-derived ovarian cancer cell lines of all epithelial subtypes. Notably, we found that most of the cell lines were sensitive to VSV virotherapy. With the objective of improving treatment efficacy for the oncolytic virus-resistant cell lines, we tested various combinations with ovarian cancer standard of care drugs: olaparib, carboplatin, paclitaxel, doxorubicin, cyclophosphamide, and gemcitabine. While none of these combinations revealed to be beneficial, further experiments demonstrated that the antiviral interferon pathway was functional in VSV-resistant cell lines. Given that interferons signal through Janus kinase (JAK)-STAT to mediate their antiviral function, we tested combinations of oncolytic VSV with clinically relevant JAK inhibitors. Our results show that combining VSV with various JAK inhibitors, including ruxolitinib, enhances VSV virotherapy and treatment efficacy. Altogether, we show that VSV, either as a stand-alone treatment or in combination with JAK inhibitors provides an effective therapeutic option for ovarian cancer patients.